2012
DOI: 10.1002/da.21974
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic Versus Diagnosis-Specific CBT for Anxiety Disorders: A Preliminary Randomized Controlled Noninferiority Trial

Abstract: BACKGROUND Transdiagnostic cognitive-behavioral treatments for anxiety disorders have been gaining increased attention and empirical study in recent years. Despite this, research on transdiagnostic anxiety treatments has, to date, relied on open trials, or comparisons to waitlist conditions, published benchmarks, or relaxation-based interventions. METHODS The current study was a randomized clinical trial examining the efficacy of a 12-week transdiagnostic cognitive-behavioral group treatment in comparison to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
133
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(140 citation statements)
references
References 47 publications
5
133
1
1
Order By: Relevance
“…Except for 6 studies that only reported the changes in anxiety Norton & Barrera, 2012;Titov et al, 2010 [1&2]), effect sizes for both anxiety and depression outcomes were calculated in all studies. The measures chosen to calculate the effect sizes were the ones present to a greater extent in the majority of included studies (Table 1), and most of the times were the ones defi ned by the studies' authors as principal outcome measures.…”
Section: Summary Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for 6 studies that only reported the changes in anxiety Norton & Barrera, 2012;Titov et al, 2010 [1&2]), effect sizes for both anxiety and depression outcomes were calculated in all studies. The measures chosen to calculate the effect sizes were the ones present to a greater extent in the majority of included studies (Table 1), and most of the times were the ones defi ned by the studies' authors as principal outcome measures.…”
Section: Summary Measuresmentioning
confidence: 99%
“…Concerning the 21 included RCTs, 20 studied adults whereas only 1 , which used WLC, included participants younger than 18 years of age. Out of the 20 RCTs with adults, 13 studies involved WLC (Bolton et al, 2014;Chu et al, 2016;Newby et al, 2013 (1); Norton, Hayes, & Hope, 2004;Norton & Hope, 2005;Schmidt et al, 2012; (1); Wuthrich & Rapee, 2013), one study used a discussion group for comparison (Wuthrich, Rapee, Kangas, & Perini, 2016), one used TAU for comparison , one used relaxation training , and fi ve studies compared T-CBT with disorder-specifi c CBT (Dear et al, 2015;Lotfi , Bakhtiyari, Asgharnezhad-Farid, & Amini, 2014;Norton & Barrera, 2012;Titov et al, 2015b). The study characteristics can be found in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their systematic review and meta-analysis, (Newby et al, 2015) concluded that transdiagnostic approaches are as effective as disorder specific treatments for treating anxiety and may be superior for reducing depression. Similarly, Norton & Barrera (2012) observed treatment equivalence between disorder specific and transdiagnostic treatments for anxiety in a non-inferiority randomised controlled trial (RCT).…”
mentioning
confidence: 95%
“…In their systematic review and meta-analysis, (Newby et al, 2015) concluded that transdiagnostic approaches are as effective as disorder specific treatments for treating anxiety and may be superior for reducing depression. Similarly, Norton & Barrera (2012) observed treatment equivalence between disorder specific and transdiagnostic treatments for anxiety in a non-inferiority randomised controlled trial (RCT).We have developed a transdiagnostic cognitive behavioural approach for PPS which can also be used for long-term conditions. We anticipate that the adapted transdiagnostic approach may address the need for efficiency while maintaining the efficacy of larger effects seen in specific condition treatment programmes.…”
mentioning
confidence: 99%